Análisis del desempeño de señales digitales con Fec Reed Solomon utilizando USRP (Universal Software Radio Peripheral) 2920 como transceiver. - Zapata Yacelga, Ricardo Israel (2017)
The paper presents the experimental study of the application of correction of errors in access networks using software defined radio transceivers based on the USRP. The system was tested in a wireless link to 1 m and an improvement was obtained in the yield of 4 dB for BPSK modulation formats and QPSK when a Reed Solomon code (127, 123) is added to reduce errors. A characterization of the USRP is also presented as a transceiver.